1999
DOI: 10.1046/j.1463-5224.1999.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasculature of the orbital rete in the Japanese deer (Cervus nippon)

Abstract: The vasculature of the orbital rete (rete mirabile ophthalmicum) in Japanese deer (Cervus nippon) was studied using corrosion casting, scanning electron microscopy, and histology. The orbital rete is a flat, triangular- or leaf-shaped arterial network, which consists of a complex of small arterioles, that intermixes with a similar complex of the supraorbital vein at the base of the orbital cavity. Blood to the retina passes through the orbital rete. The orbital retial arterioles leave the parent external ophth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This is the only characteristic differentiating cetaceans from terrestrial mammals (e.g. deer, 8,9 pronghorn, 8 elk 8 ) and birds (pigeon, 10 night heron 11 ): the rete is located at a short distance behind the orbit and is bathed in venous blood from the orbit, relating to thermoregulation by the countercurrent heat exchange mechanism. The arterial branching and elaborate vasculature of the cetacean ophthalmic rete suggest that this organ exerts a flow‐damping effect by maintaining resistance to blood flow 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the only characteristic differentiating cetaceans from terrestrial mammals (e.g. deer, 8,9 pronghorn, 8 elk 8 ) and birds (pigeon, 10 night heron 11 ): the rete is located at a short distance behind the orbit and is bathed in venous blood from the orbit, relating to thermoregulation by the countercurrent heat exchange mechanism. The arterial branching and elaborate vasculature of the cetacean ophthalmic rete suggest that this organ exerts a flow‐damping effect by maintaining resistance to blood flow 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been shown that in harbor seals ( Phoca vitulina ) the tactile hair follicles, which are supplied with a plentiful volume of blood, are selectively heated and play a role as a thermoregulatory structure responsible for the maintenance of high tactile sensitivity at extremely low ambient temperatures 6,7 . The ophthalmic rete of artiodactyla is suggested to control the temperature of arterial blood to the eye 8,9 . The rete in birds also plays an important role in reducing heat loss from the eye by a counter‐current heat exchange mechanism 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…The rete chiasmaticum and its extension onto the proximal portion of the optic nerve was termed the "internal ophthalmic rete" by McFarland et al, (1979) due to its intracranial nature, while the internal ophthalmic rete that we describe above was called the "external ophthalmic rete" by McFarland et al, (1979) due to its extracranial nature. Other names used in the literature include "ophthalmic rete," "external orbital rete," and "infraorbital rete" (Slijper, 1936;Nakajima, 1961;Fisher, 1981, 1982;Melnikov, 1997;Ninomiya and Masui, 1999;Ninomiya et al, 2014). In our specimens, the extracranial ophthalmic rete was well injected through contribution from the rete chiasmaticum while the contribution from the external ophthalmic artery appeared comparatively modest.…”
Section: Anatomic Considerationsmentioning
confidence: 47%
“…In the ox (Bos taurus) (Steven 1964) and Japanese deer (Cervus nippon), (Ninomiya and Masui 1999), these vessels originate from the anterior part of the rete mirabile of the carotid artery and accompany the intracranial optic nerve. In yak (Bos grunnines) and sheep (Ovis aries), the ophthalmic artery originates from the rete chiasmaticum = part of the rostral epidural rete mirabile (Simoens and Ghoshal 1981;Shao et al 2007).…”
Section: Discussionmentioning
confidence: 99%